Pathophysiological Responses of Chickens to very Virulent Infectious Bursal Disease Virus Infection: Haematological Modulation by Nigella sativa: Haematological Effects of Nigella sativa in vvIBDV-Challenged Chickens - Muhammed, Muhammed Shuaib; Orakpoghenor, Ochuko; Elijah, Mary Oluwatomisin; Oladele, Sunday Blessing; Mohammed, Bisalla; Musa, Ibrahim Waziri (Veterinary Biomedical and Clinical Journal, 2025)
Despite growing interest in the immunomodulatory properties of Nigella sativa, limited evidence exists on its haematological effects during very virulent infectious bursal disease virus (vvIBDV) infection in chickens. This study evaluated the influence of N. sativa seed powder (NSSP) on haematological parameters in Dominant Black Marshal cockerels experimentally challenged with vvIBDV. One hundred one-day-old chicks were randomly assigned to five groups (A–E, 20 birds each). Groups A and B received basal diet only; C and D received 2.8 g/kg NSSP from 21–27 days of age (doa); and E received NSSP continuously from 1–42 doa. On day 28, groups B, D, and E were orally challenged with vvIBDV, while A and C remained unchallenged. Blood samples collected from 1–42 doa were analysed for packed cell volume (PCV), haemoglobin concentration (Hb), red blood cell (RBC), total leukocyte (TLC), differential leukocyte counts, and heterophil/lymphocyte (H/L) ratios. Groups receiving NSSP generally showed higher PCV, Hb, and RBC prior to challenge. Following vvIBDV infection, significant (P < 0.05) declines in PCV, Hb, and RBC were observed in groups B, D, and E, with group B showing the most pronounced anaemia. Groups D and E demonstrated moderate leukocytosis and lower H/L ratios compared to group B, suggesting reduced stress and inflammatory responses. These findings indicate that N. sativa supplementation, particularly when administered from early life, may confer partial haematological protection and mitigate the adverse effects of vvIBDV infection in chickens.